Lipoprotein lipase and angiopoietin-like 4 – Cardiomyocyte secretory proteins that regulate metabolism during diabetic heart disease. (June 2015) - Puthanveetil, Prasanth; Wan, Andrea; Rodrigues, Brian
Abstract Cardiac diseases have been extensively studied following diabetes and altered metabolism has been implicated in its initiation. In this context, there is a shift from glucose utilization to predominantly fatty acid metabolism. We have focused on the micro- and macro-environments that the heart uses to provide fatty acids to the cardiomyocyte. Specifically, we will discuss the cross talk between endothelial cells, smooth muscles and cardiomyocytes, and their respective secretory products that allows for this shift in metabolism. These changes will then be linked to alterations in the cardiovascular system and the augmented heart disease observed during diabetes. Traditionally, the heart was only thought of as an organ that supplies oxygen and nutrients to the body through its function as a pump. However, the heart as an endocrine organ has also been suggested. Secreted products from the cardiomyocytes include the natriuretic peptides atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP). Both have been shown to have vasodilatory, diuretic and antihypertensive effects. These peptides have been extensively studied and their deficiency is considered to be a major cause for the initiation of cardiovascular and cardiometabolic disorders. Another secretory enzyme, lipoprotein lipase (LPL), has been implicated in diabetic heart disease. LPL is a triglyceride-hydrolyzing enzyme that is synthesized within the cardiomyocyte and secreted towards the lumen under various conditions. For example, moderate or short-term hyperglycemia stimulates the release of LPL from the cardiomyocytes towards the endothelial cells. This process allows LPL to contact lipoprotein triglycerides, initiating their break down, with the product of lipolysis (free fatty acids, FA) translocating towards the cardiomyocytes for energy consumption. This mechanism compensates for the lack of glucose availability following diabetes. Under prolonged, chronic conditions of hyperglycemia, there is a need to inhibit this mechanism to avoid the excess delivery of FA to the cardiomyocytes, an effect that is known to induce cardiac cell death. Thus, LPL inhibition is made possible by a FA-induced activation of PPAR β/δ, which augments angiopoietin-like 4 (Angptl4), an inhibitor of LPL activity. In the current review, we will focus on the mediators and conditions that regulate LPL and Angptl4 secretion from the cardiomyocyte, which are critical for maintaining cardiac metabolic homeostasis.